The case law of the European Court of Human Rights: Its content and effect on suicide prevention in custody and detention - Cliquennois, Gaëtan (Criminologie)

(untitled) (Les Presses de l’Université de Montréal, 2022)
This article analyses developments in case law based on Article 2 (right to life) in the European Court of Human Rights as they relate to suicide prevention for those in detention (in prison, police stations, or psychiatric hospitals) and the paradoxical effects they have had on prevention policies enacted by states condemned by the Court. I first show that the jurisprudential philosophy used by the Court is characterized by an emphasis on risk management and a narrow understanding of individual motivations for suicide. I then demonstrate that, under pressure from the Committee for the Prevention of Torture and the national associations for the defence of the rights of detainees, the Court’s judgments have led states to adopt suicide prevention policies that are actuarial (based on risk management) and punitive. However, this perverse effect seems to be partially offset by the possibility that the families of detainees, through the investigative duties of member states of the Council of Europe, can exercise at least some supervision over the custodial and police systems.